2014
DOI: 10.1037/a0034455
|View full text |Cite
|
Sign up to set email alerts
|

Auto-catégorisation ethnique, attitudes d’acculturation et représentations sociales chez les jeunes Français issus de l’immigration.

Abstract: Cette recherche explore les modes d'auto-catégorisation et les attitudes d'acculturation des jeunes Français issus de l'immigration maghrébine (n ϭ 334) comparativement a `leurs pairs issus de l'immigration turque (n ϭ 158). Les premiers ont davantage recours a `l'auto-catégorisation ethnique que les seconds. En ce qui concerne les attitudes d'acculturation de l'ensemble de ces jeunes, ils refusent l'assimilation et le repli communautaire et optent pour l'intégration, et ce, quels que soient leur sexe, leur âg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Amin and Vinet (2014) showed that if integration is usually the most chosen orientation among both North African and Turkish students, North Africans are significantly more oriented towards integration but less oriented towards separation than Turkish students. This is consistent with some studies showing that in Germany, the first European country of Turkish immigration, Turks are the ethnic group that, unlike other groups, expresses the strongest preference for separation (Ersanilli and Koopmans 2011).…”
Section: North African and Turkish Immigrants In France And Their Accmentioning
confidence: 97%
“…Amin and Vinet (2014) showed that if integration is usually the most chosen orientation among both North African and Turkish students, North Africans are significantly more oriented towards integration but less oriented towards separation than Turkish students. This is consistent with some studies showing that in Germany, the first European country of Turkish immigration, Turks are the ethnic group that, unlike other groups, expresses the strongest preference for separation (Ersanilli and Koopmans 2011).…”
Section: North African and Turkish Immigrants In France And Their Accmentioning
confidence: 97%